Novel techniques in sensory characterization and consumer profiling - Varela Tomasco, Paula; Ares, Gaston (CRC Press, 2014)
"Sensory characterization is one of the most powerful, sophisticated and extensively applied tools in sensory science. This book focuses on sensory characterization of food and non-food products, providing an overview of classical and novel alternative methodologies. A complete description of the methodologies would be provided. Each description would be accompanied by detailed information for their implementation, discussion of examples of applications and case-studies. The implementation of the majority of the methodologies would be performed in the statistical free software R, which would make the book very useful for people non-familiar with complex statistical software"-- Provided by publisher.
Keywords: Food -- Sensory evaluation.; Sensory evaluation.; Marketing research.; New products.; elektronické knihy; electronic books